A polyimide based all-organic sodium ion battery1. Issue 19 (21st May 2015) - Banda, Harish; Damien, Dijo; Nagarajan, Kalaivanan; Hariharan, Mahesh; Shaijumon, Manikoth M.
<x xml:space="preserve">Abstract</x> N, N′-diamino-3, 4, 9, 10-perylenetetracarboxylic polyimide (PI) based materials show excellent electrochemical performance as cathodes for sodium-ion batteries and an all-organic sodium ion battery using this polyimide as the cathode and disodium terephthalate (NaTP) (pre-sodiated) as the anode is demonstrated.